Effect of humin-urea-rock phosphate amendment on Bekenu series (Tipik Tualemkuts) soil - Perumal, Palanivell; Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2012)
Application of crude humin with urea and Egyptian rock phosphate (ERP) may reduce ammonia loss from urea. This study was conducted to determine the effect of mixing crude humin with urea and ERP on ammonia volatilization and selected soil chemical properties. Crude humin from four different composts was mixed with urea and ERP and ammonia loss from these treatments were evaluated using the closed-dynamic air flow system. Standard procedures were used to determine ammonia loss, soil pH, total nitrogen, exchangeable ammonium, available nitrate, exchangeable phosphorus, cations, organic matter, total organic carbon and cation exchange capacity. Amending urea with crude humin had no effect on total amount of ammonia loss. However, addition of the crude humin significantly increased pH, organic matter, total organic carbon, cation exchange capacity (CEC) and exchangeable cations of Bekenu series (Tipik Tualemkuts). Crude humin from selected waste compost can be used to improve soil chemical properties.